Proposal of a new 'resect and discard' strategy using magnifying narrow band imaging: Pilot study of diagnostic accuracy. (April 2014) - Takeuchi, Yoji; Hanafusa, Masao; Kanzaki, Hiromitsu; Ohta, Takashi; Hanaoka, Noboru
Abstract : Background and Aim: A 'resect and discard' strategy using non‐magnifying narrow band imaging (N‐NBI) has been proposed for reducing screening colonoscopy costs, but it does not take into consideration advanced histology and magnifying NBI (M‐NBI) that can potentially further improve the 'resect and discard' strategy. We conducted a pilot study to investigate the feasibility of M‐NBI for the new 'resect and discard' strategy with consideration for advanced histology. Methods: The present study involved 63 patients. For each polyp, optical diagnosis was independently made using N‐NBI and M‐NBI, a decision (discard or send for pathology) was made based on the M‐NBI findings, and histological and optical diagnosis results were compared. Results: Sensitivity, specificity and accuracy (95% confidence interval) of M‐NBI for lesions with advanced histology were 1.00 (0.36–1.00), 0.92 (0.91–0.92) and 0.92 (0.90–0.92), respectively. Whereas the management of 86% of small polyps could be decided without formal histopathology, lesions with advanced histology were not discarded using M‐NBI. The diagnostic accuracy of M‐NBI in distinguishing neoplastic from non‐neoplastic lesions was higher than that of N‐NBI. Conclusions: We propose a new resect and discard strategy with advanced histology using M‐NBI that is a promising strategy to reduce the costs of histopathology and to minimize the risk of discarding important lesions.